EXPLORING THE IMPACT OF NEW MEDIA EXPOSURE ON YOUTH FOR SOCIETAL AND SUSTAINABLE DEVELOPMENT IN RURAL AREAS: A STUDY IN TIRUCHIRAPPALLI DISTRICT - E. V. Prabha (International Journal of Research -GRANTHAALAYAH, 2025)
Technology is advancing rapidly, and youth are increasingly exposed to new media and their diverse applications. This exposure varies by individual, but overall, young people—especially in rural areas—are becoming more adept at engaging with electronic media. As digital content proliferates, it becomes essential to understand how rural youth interact with new media and how this interaction influences societal and sustainable development. This study aims to explore the extent and nature of new media exposure among youth in rural villages of Tiruchirappalli district. The study focuses on a qualitative approach to provide a comprehensive analysis. The findings will contribute to understanding the role of youth in leveraging technology for positive societal impact and rural sustainability.